63 USING CO-DESIGN TO DEVELOP A CORE COMPETENCY FRAMEWORK FOR INTERPROFESSIONAL COLLABORATION WITHIN INTEGRATED CARE TEAMS FOR OLDER PEOPLE IN IRELAND. (18th November 2021) - O'Donoghue, G; Shé, É N; O'Shea, M; Donnelly, S; O'Donnell, D
Abstract: Background: Fundamental to the successful delivery of integrated care for older people in Ireland and internationally, is sustainable interprofessional collaboration (IPC). Current evidence, however, offers little guidance in terms of how IPC can be fostered and sustained within the context of integrated care and older people. This research aimed to design a framework that describes core competencies for IPC within integrated care teams (ICTs) for older people, and outline mechanisms by which ICTs could start to develop the necessary knowledge, skills and behaviours to demonstrate proficiency. Methods: Using a co-design approach, academic health systems researchers, members of the National Integrated Care Programme for Older People in Ireland (IPC subcommittee), and public and patient representatives (nominated by Age Friendly Ireland) collaborated across three studies to devise a core competency framework. Study 1 used co-design workshops to develop and gain consensus on core competencies; study 2 employed semi-structured interviews to explore current working practice within two existing interprofessional ICTs and study 3, combined findings from study 1 and 2, validated the agreed upon competencies and finalised the IPC competency framework. Results: Six competencies, within three domains, were agreed. Domain one, knowledge of the team, includes the competencies, understanding roles and making referrals. Domain two, communication, includes sharing information and communicating effectively and domain three, shared decision-making, includes the final two competencies, supporting decision making with older people and collective clinical decision-making. Conclusion: This co-designed framework provides the scaffold for curriculum development for the training of health and social care professionals around interdisciplinary team working for the care of older people. The core competencies prioritise mutual respect and active elicitation of input from all disciplines, thereby empowering disciplinary-specific expertise. Finally, and perhaps most critically, the will and preferences of the older person are deemed central to effective integrated interprofessional working within the developed IPC framework.